Characterization of silver carp (Hypophthalmichthys molitrix) myosin protein glycated with konjac oligo-glucomannan. (June 2016) - Liu, Jianhua; Xu, Qiuhong; Zhang, Jingjing; Zhao, Peicheng; Ding, Yuting
Abstract: Silver carp ( Hypophthalmichthys molitrix ) myosin protein (Ms) was glycated with konjac oligo-glucomannan (KOG) by using the controlled Maillard reaction (MR). Colorimeter measurements and SDS-PAGE analysis indicated the occurrence of the MR and glycoconjugates formation, respectively. Thinner sheet and non-homogeneous Ms-KOG conjugates were observed by scanning electron microscope (SEM). Fourier transform infrared spectroscopy (FT-IR) indicated that the amide I, II and III bands of Ms were changed by the glycation. Glycation lowered the isoelectric point from 5.3 to 3.8 when incubated for 96 h. Ms became highly soluble in 0.1 M NaCl with the decrease of 23.6% of the total lysine residues at the reaction time of 12 h. The thermal stability of Ms glycated with KOG for 24 h was effectively improved from 61.4% to 95.8% when heated at 80 °C for 60 min. These results suggested that MR with KOG can be a promising way to improve functional properties of Ms. Graphical abstract: Highlights: KOG was glycated with silver carp Ms by using the controlled Maillard reaction. Thinner sheet and non-homogeneous Ms-KOG conjugates were observed by SEM. Glycation significantly lowered the pI and enhanced the solubility of Ms. Thermal stability of Ms glycated with KOG was effectively improved. Steric hindrance of KOG might be the factor improving the functionality of Ms.